The effectiveness of moringa leaf jelly on mother's prolactin level and baby's outcome - Marsiami, Azizati Salmas; Puspariny, Cynthia (International Journal of Public Health Science (IJPHS), 2024)
The failure of exclusive breastfeeding and the increased use of milk formulas is one of the results of a shortage of breast milk production. Moringa leaf contains phytosterol to increase milk production. Fortification of moringa leaf with jelly will increase the nutritional value of moringa leaf so that the prolactin increases and the production and quality of breast milk get better for babies. This study aimed to determine the effect of moringa leaf jelly on increasing milk production (prolactin, breast milk volume), and the outcome for the baby. Quasi-experimental research using pre-postest with control group design. The study respondents were taken with a purposive sampling technique of 58 people. Outcome indicators for babies are seen from the baby’s weight, the baby's urination frequency, the baby's defecation, and the baby's sleep duration. There was a significant effect on the increase in prolactin score by 23.3%, breast milk volume by 47%, and outcome babies by 3.3% in respondents given moringa leaf jelly. Meanwhile, respondents who were not given Moringa leaf jelly had a risk of decreasing prolactin levels 10.5 times, breast milk supply was 3.8 times lower and the outcomes for babies were 15 than those given Moringa leaf jelly. The moringa leaf jelly significantly effects increasing milk production and outcomes for babies compared to standard interventions.